ANALISA PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN (Students' Journal of Accounting and Banking, 2012)
This research is to examine the effect of the CAR, RORA, BOPO and LDR ratio on stock prices at the banking company listed on the Stock Exchange.The population in this study are listed banking companies in Indonesia Stock Exchange (BEI) in 2007-2010. Sampling technique using a purposive sampling technique according to established criteria contained 22 samples. Analysis technique used is multiple regression analysis.The results showed that the ratio RORA had positive influence stock prices, the ratio of CAR had negative influence,while the ratio BOPO, and LDR hadn’t influence on stock prices.Keywords: CAR, RORA, OEOI, LDR , Stock Price.